2017
DOI: 10.1007/s00360-017-1088-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat stress on the renal and branchial carbohydrate metabolism and antioxidant system of Antarctic fish

Abstract: The objective of the present study was to assess the effect of short-term (2-144 h) heat stress (8 °C) on energy production processes and antioxidant defense systems in the kidneys and gills of Notothenia rossii and Notothenia coriiceps. Heat stress affected energy metabolism and oxidative stress parameters in a time-, tissue-, and species-dependent manner, and gills were more sensitive than kidneys to heat stress. N. rossii kidneys were able to stabilize carbohydrate metabolism after 12 h of heat stress, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 89 publications
0
24
1
Order By: Relevance
“…The increased risk of SGA in summer may be the result of high-temperature exposure. Heat stress could cause damage to the antioxidant defense system and result in a larger secretion amount of oxytocin (Forgati et al 2017), which could have a negative impact on maternal health and fetal growth. The association in winter could be explained by a deficiency in vitamin D. Vitamin D has been found to be negatively correlated to SGA risk (Wang et al 2018), and the level of vitamin D in winter in China is much lower than that in summer (Yang and Zhang 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of SGA in summer may be the result of high-temperature exposure. Heat stress could cause damage to the antioxidant defense system and result in a larger secretion amount of oxytocin (Forgati et al 2017), which could have a negative impact on maternal health and fetal growth. The association in winter could be explained by a deficiency in vitamin D. Vitamin D has been found to be negatively correlated to SGA risk (Wang et al 2018), and the level of vitamin D in winter in China is much lower than that in summer (Yang and Zhang 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As pregnant women are particularly sensitive to meteorological conditions and environmental exposure [5], the period before delivery could be a critical window in uencing fetal growth when high or low ambient temperature exposure occurs [23]. In summer, heat stress can damage antioxidant defense systems and lead to increased oxytocin secretion [24]. In winter, decreased sunlight exposure may lead to lower levels of vitamin D [25], which is essential for normal placental function and fetal growth [26].…”
Section: Discussionmentioning
confidence: 99%
“…Other genes expressed by heat stress, such as activator protein 1 (AP-1), CCAAT enhancer binding protein beta (CEBP), IKBA, and NF-kB, exert major effects by inducing inflammation, apoptosis, and cell survival [43]. Several studies have reported that heat stress affects glucose and lipid metabolism, which may help to maintain energy homeostasis in fish [7,44].…”
Section: Discussionmentioning
confidence: 99%
“…p73, which is a component in the direct negative feedback loop in the p53 signaling pathway [5,17], was more highly expressed in the HT group compared to the NT group, suggesting that it may have suppressed p53 activities by repression or competition of p53 transcriptional activation. Meanwhile, thrombospondin-1 (TSP1), which is important for interfacing with stress signals to inform stress responses in tissue [44,48], was less expressed in the HT group than in the NT group. The CD82 antigen, KAI, is a member of the tetraspanin protein family that regulates cell motility, morphology, signaling, and cell survival [49,50], and this antigen was also expressed at lower levels in the HT group.…”
Section: Discussionmentioning
confidence: 99%